The Immunophilin-Interacting Protein AtFIP37 from Arabidopsis Is Essential for Plant Development and Is Involved in Trichome Endoreduplication - Vespa, Laurent (American Society of Plant Biologists, 2004)
The FKBP12 (FK506-binding protein 12 kD) immunophilin interacts with several protein partners in mammals and is a physiological regulator of the cell cycle. In Arabidopsis, only one specific partner of AtFKBP12, namely AtFIP37 (FKBP12 interacting protein 37 kD), has been identified but its function in plant development is not known. We present here the functional analysis of AtFIP37 in Arabidopsis. Knockout mutants of AtFIP37 show an embryo-lethal phenotype that is caused by a strong delay in endosperm development and embryo arrest. AtFIP37 promoter::β-glucuronidase reporter gene constructs show that the gene is expressed during embryogenesis and throughout plant development, in undifferentiating cells such as meristem or embryonic cells as well as highly differentiating cells such as trichomes. A translational fusion with the enhanced yellow fluorescent protein indicates that AtFIP37 is a nuclear protein localized in multiple subnuclear foci that show a speckled distribution pattern. Overexpression of AtFIP37 in transgenic lines induces the formation of large trichome cells with up to six branches. These large trichomes have a DNA content up to 256C, implying that these cells have undergone extra rounds of endoreduplication. Altogether, these data show that AtFIP37 is critical for life in Arabidopsis and implies a role for AtFIP37 in the regulation of the cell cycle as shown for FKBP12 and TOR (target of rapamycin) in mammals.